2016
DOI: 10.3389/fpsyt.2016.00013
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Positive Emotions Program for Schizophrenia: An Intervention to Improve Pleasure and Motivation in Schizophrenia

Abstract: ObjectivesThe efficacy of drug-based treatments and psychological interventions on the primary negative symptoms of schizophrenia remains limited. Recent literature has distinguished negative symptoms associated with a diminished capacity to experience, from those associated with a limited capacity for expression. The positive emotions program for schizophrenia (PEPS) is a new method that specifically aims to reduce the syndrome of a diminished capacity to experience.MethodsThe intervention’s vital ingredients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 70 publications
0
30
0
2
Order By: Relevance
“…Although some clinical studies have specifically targeted positive mental imagery (Blackwell et al ., ; Murphy et al ., ), and observed effects on behavioural activation (Renner, Ji, Pictet, Holmes, & Blackwell, ), these have not been for actual events that individuals might engage in their daily lives. Although conceptions (Nguyen et al ., ) and pilot studies (Favrod, Giuliani, Ernst, & Bonsack, ; Favrod et al ., ) of such targeted interventions have emerged, applied research is still in early stages. Introducing mental simulations to induce an anticipatory hedonic response might prove to enhance treatments such as behavioural activation; however, this is yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although some clinical studies have specifically targeted positive mental imagery (Blackwell et al ., ; Murphy et al ., ), and observed effects on behavioural activation (Renner, Ji, Pictet, Holmes, & Blackwell, ), these have not been for actual events that individuals might engage in their daily lives. Although conceptions (Nguyen et al ., ) and pilot studies (Favrod, Giuliani, Ernst, & Bonsack, ; Favrod et al ., ) of such targeted interventions have emerged, applied research is still in early stages. Introducing mental simulations to induce an anticipatory hedonic response might prove to enhance treatments such as behavioural activation; however, this is yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although some clinical studies have specifically targeted positive mental imagery (Blackwell et al, 2015;Murphy et al, 2015), and observed effects on behavioural activation (Renner et al, 2017), these have not been for actual events that individuals might engage in their daily lives. Although conceptions (Nguyen et al, 2016) and pilot studies (Favrod et al, 2010;Favrod et al, 2015) of such targeted interventions have emerged, applied research is still in early stages. Introducing mental simulations to induce an anticipatory hedonic response might prove to enhance treatments such as behavioural activation, however, this is yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…conceived the programme. The intervention development and the programme description have been published [27]. The French version of PEPS can be downloaded for free at www.seretablir.net/peps/.…”
Section: Methodsmentioning
confidence: 99%
“…The Positive Emotions Programme for Schizophrenia (PEPS) was developed in response to these issues [27]. PEPS is an intervention consisting of 8 one-hour sessions applied to groups of 5–10 participants.…”
Section: Introductionmentioning
confidence: 99%